Application of IP Security and Mac Address Filtering Authentication Methods to Build Encrypted Interconnection Networks: Application of IP Security and Mac Address Filtering Authentication Methods to Build Encrypted Interconnection Networks - Mochamad Akbar Fajar Hidayat Putra; Ucuk Darusalam; Andri Aningsih (Jurnal Mantik, 2020)
The development of the industry is happening very fast, Making the company must improve its resource capabilities, one of which is the technology used to be able to contribute to the company. Security issues become very important at this time, especially for companies that already have many branches in different locations that require high-performance security systems, because the network interconnections that occur between the head office and branch offices are very vulnerable to attacks from irresponsible parties, The use of IP Security and MAC Address Filtering authentication methods on network devices is very useful to be able to protect, verify and filter company data from enemies on the internet. IP Security authentication provides integrity between connections, then Filtering MAC Address can help the router task to be able to recognize users on the network, So that expected the combination between IP Security and Mac Address Filtering will provide security for every transfer and receive data from Headquarter to branch office, then the company doesn't have to worry about data package being robbed or manipulated by the irresponsible parties.